The Impact of Armed Conflicts on Military Food Security - Pînzariu Sorin (Scientific Bulletin, 2025)
Armed conflicts represent one of the biggest challenges faced by food management systems within military forces. Disruption of supply networks, destruction of infrastructure and difficult terrain conditions can have a significant impact on the ability to provide safe and nutritious food for staff. This article explores how armed conflict affects food security in the context of military operations, looking at key challenges and innovative risk mitigation strategies. The findings emphasize the need for an interdisciplinary approach to guarantee food security and the health of fighting troops during armed conflicts.